{Furanyl nucleosides: synthesis and kinetics of their formation} - Chatgilialoglu, Chryssostomos; Vrantza, Despoina; Gimisis, Thanasis (Tetrahedron Lett., 2004)
The thermal reaction (at 140°C) of various 1′,2′-didehydro- 2′-deoxynucleosides afforded the corresponding furanyl nucleosides in good yields. The reaction kinetics were monitored by 1H NMR and the mechanism in terms of 'four-center complex fission' is discussed. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Kinetics; Nucleosides; Reaction mechanism; [Furans